2018
DOI: 10.5770/cgj.21.304
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Brain Training Pilot Study For People With Mild Cognitive Impairment

Abstract: ObjectiveA pilot study to determine the feasibility of recruiting patients with MCI to test for cognitive interventions.MethodThirty patients with amnestic MCI were to be divided into two intervention arms and one control group. Participants went to local sites and completed brain training for one hour three times per week for nine weeks. Outcome measures were: recruitment, computer abilities, compliance, task performance, neuropsychological tests, and electroencephalography.ResultsAfter six months, only 20 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…For the current study, no treatment effects were observed for the cognitive secondary outcome, Total Scale score on the RBANS, which was the primary outcome in Barnes et al 7 and Knoefel et al 10 . It may not be surprising that this secondary outcome did not improve with training, as this RBANS score is a global composite of memory, attention, visual perception and construction, and language, and the exercises in BrainHQ primarily engage more focused cognitive skills (e.g., auditory attention and memory).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…For the current study, no treatment effects were observed for the cognitive secondary outcome, Total Scale score on the RBANS, which was the primary outcome in Barnes et al 7 and Knoefel et al 10 . It may not be surprising that this secondary outcome did not improve with training, as this RBANS score is a global composite of memory, attention, visual perception and construction, and language, and the exercises in BrainHQ primarily engage more focused cognitive skills (e.g., auditory attention and memory).…”
Section: Discussioncontrasting
confidence: 50%
“…For example, Barnes et al 7 failed to find an immediate treatment effect on their primary cognitive outcome in 47 subjects with MCI. Similarly, Gooding et al 9 and Knoefel et al 10 reported minimal improvements on cognitive tests for their experimental conditions compared to active control groups. However, the current results are at odds with recent meta-analyses that have shown small to medium effects of various cognitive interventions in patients with MCI.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors for one study were contacted for additional data as their original article data were not suitable for analysis (combined means and standard deviations across training and control group). As no further information was provided, the study was included in the review but not the meta-analysis (Knoefel et al, 2018).…”
Section: Missing Datamentioning
confidence: 99%
“…206). Knoefel et al (2018) identified and recruited participants through review of memory clinic data; three authors of the study then confirmed diagnosis of MCI after baseline testing, but the criteria used were not reported. All other studies applied similar diagnostic criteria to establish a diagnosis of MCI: i) self-or informant-reports of memory complaints, ii) objective memory impairments (assessed via performance on neuropsychological tests), iii) does not meet diagnostic criteria for dementia, and iv) preserved activities of daily living.…”
Section: Participantsmentioning
confidence: 99%